Influence of form deviations on the tolerance analysis - Chahbouni, Mouhssine; Boutahari, said; Amegouz, Driss (International Journal of Engineering and Technology, 2014)
The objective of this paper is to present the influence of form deviations on the tolerance analysis of an assembly. For this we will study initially the tolerance analysis using the deviations and clearances domains method, a second time we will integrate the influence of form tolerances on the allowable deviation domain. To illustrate this analysis we used a classical assembly with position and form tolerances (coaxiality and cylindricity). Finally a comparative study between the two cases was illustrated. Keywords:Tolerance Analysis, CAD/CAM, Assembly Systems, Engineering Drawings.